2013
DOI: 10.1007/s00423-013-1089-y
|View full text |Cite
|
Sign up to set email alerts
|

Early enteral nutrition after pancreatoduodenectomy: a meta-analysis of randomized controlled trials

Abstract: Current RCTs suggests that early EN appears safe and tolerated for patients after PD, but does not show advantages in infection and postoperative hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Feeding jejunostomy can also slow intestinal motility . Although a recent meta‐analysis of randomized controlled trials found that early enteral nutrition after PD did not increase DGE incidence , foreign body placement in the afferent loop of the jejunum can disturb its recovery or motility. Prevention of intraoperative blood loss and stent placement at CJ through the RTBD route might reduce the incidence of primary DGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding jejunostomy can also slow intestinal motility . Although a recent meta‐analysis of randomized controlled trials found that early enteral nutrition after PD did not increase DGE incidence , foreign body placement in the afferent loop of the jejunum can disturb its recovery or motility. Prevention of intraoperative blood loss and stent placement at CJ through the RTBD route might reduce the incidence of primary DGE.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan–Meier survival curve estimates and log–rank tests were used to compare survival rates. Cox proportional hazards analyses were carried out to estimate the total effect of DGE on cancer‐specific survival adjusted for the following potential risk factors: age, primary disease for which PD was indicated, the Union for International Cancer Control pathological stage of primary disease , presence of diabetes mellitus, and DGE grade. All P ‐values were two‐sided, and P < 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in the present study, the impact of enteral nutrition on the postoperative course was investigated without focusing on nutritional status. A recent meta‐analysis of routine enteral nutrition compared with other nutritional routes after pancreatoduodenectomy showed that enteral nutrition has no advantages in terms of postoperative outcomes. Nevertheless, the ISGPS guidelines recommend enteral nutrition over parenteral nutrition as nutritional support in patients with postoperative complications or malnutrition following pancreatoduodenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most clinical studies have not been able to demonstrate the effectiveness of EN in the clinical course of these patients [9][10][11][12][13][14][15]. Shen et al reported that EN appeared safe and tolerable for patients after pancreatoduodenectomy, but they did not show advantages in terms of infectious complications and postoperative hospital stay by accumulation of data from recent RCTs [16]. In addition, the guidelines for preoperative care for pancreatoduodenectomy established by the Enhanced Recovery After Surgery society indicate that patients should be allowed a normal diet after pancreatoduodenectomy and that enteral tube feeding should not be placed routinely [17].…”
Section: Discussionmentioning
confidence: 99%